Pemanfaatan Serat Daun Nanas Sebagai Hairclip Utilization of Pineapple Leaf Fiber as a Hairclip - Agus Susanti; Anggraini Oktapia; Sofia Daniati (Garina, 2024)
Korespondensi: susanti@aksibukartini.ac.id Abstract. A hairclip is a hair extension that is later woven or clamped into real hair. Hairclips give a thick effect to hair. Hair clips are made from synthetic materials, one of which uses organic materials from pineapple leaf fiber waste. The aims of this research are: 1) to know the process of making hairclips using pineapple leaf fiber 2) to know and validate hairclip products using pineapple leaf fiber 3) to know the public's acceptance of hairclips using pineapple leaf fiber. The methods in this research are observation, literature, experiments, documentation, interviews and questionnaires. The experiment was carried out at Ds. Jangkungharjo RT.01 RW.01 Kec. Brati District. Grobogan, Central Java. The experiment was carried out three times, namely by coloring 1) Staining Pineapple Leaf Fibers Using Clothes Dye 2) Staining Pineapple Leaf Fibers Using Color Spray 3) Staining Pineapple Leaf Fibers Using Hair Dye. Product validation is carried out by three validators through sensory tests. The product validation results are the products in the first experiment. The results of the public test conducted on 60 respondents were that the public's level of liking for the product was 3.32, they were interested in the color of the hairclip, the level of liking for the texture was 3.17, the level of ease of use was 3.45 and the level of liking for the aroma of the hairclip was 3.12. The conclusion is that overall public acceptance is 3.26 with the description category like score. Repairs need to be made so that the hair remains strong and does not break or fall out easily and tools are needed to make the fiber making process easier..